2004
DOI: 10.1002/jbm.b.30011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser‐modified polystyrene substrate on CHO cell growth and alignment

Abstract: Biomaterial surface chemistry and nanoscale topography of biomaterials can significantly influence cell behavior in vitro. Polystyrene (PS) Petri dishes were subjected to Nd:YAG laser irradiation at 266 nm, which resulted in well-defined three-dimensional (3D) periodic nanoscale surface topographies and surface oxidation. The surface changes were analyzed by X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and a contact-angle goniometer. The samples were then used to investigate the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…1,[4][5][6][7][8][9][10][11][12] A nanostructured surface can be used to control cell differentiation and, thereby, the performance of biomaterials after implantation. [13][14][15][16] Here, we report the cellular behavior on a silicon surface, structured on the cm 2 scale by femtosecond laser ablation with high spatial frequency laser-induced periodic surfaces structures (HSF-LIPSS or HSFLs). [17][18][19][20][21] Note that silicon serves as a model surface for fundamental studies and not as typically used biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9][10][11][12] A nanostructured surface can be used to control cell differentiation and, thereby, the performance of biomaterials after implantation. [13][14][15][16] Here, we report the cellular behavior on a silicon surface, structured on the cm 2 scale by femtosecond laser ablation with high spatial frequency laser-induced periodic surfaces structures (HSF-LIPSS or HSFLs). [17][18][19][20][21] Note that silicon serves as a model surface for fundamental studies and not as typically used biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with previous work on CHO cells by Rebollar et al [55], who reported the alignment of CHO cells with a periodic surface nanostructure. CHO cells were chosen due to the fact that they are well studied, easy to culture, and so is an ideal cell type [56][57] for initial experiments on a novel substrate. We are currently working on other cell types, including primary cells, on our substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of an implanted biomaterial are of the utmost importance for its biocompatibility. As for a biomaterial surface, the cell-material interaction is strongly influenced by not only surface topography but also by surface chemistry (physicochemical property) including surface wettability (surface energy) and surface charge [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%